Microstructure and mechanical properties of extruded Mg-6.5Gd-1.3Nd-0.7Y-0.3Zn alloy - 侯秀丽 曹占义 张蕾蕾 房大庆 徐世伟 S. KAMADO 王立民 (Transactions of Nonferrous Metals Society of China, 2010)
The Mg-6.5Gd-1.3Nd-0.7Y-0.3Zn alloy ingot and sheet were prepared by casting and hot extrusion techniques,and the microstructure,age hardening behavior and mechanical properties were investigated.The results show that the as-cast alloy mainly containsα-Mg solid solution and compounds of Mg5RE and Mg24RE5（RE=Gd,Y and Nd）phases.The grain size is refined after hot extrusion,and the Mg5RE and Mg24RE5 compounds are broken during the extrusion process.The extruded alloy exhibits remarkable age hardening response and excellent mechanical properties in the peak-aging state.The ultimate tensile strength,yield strength and elongation are 310 MPa,201 MPa and 5.8%at room temperature,and 173 MPa,133 MPa and 25.0%at 300℃,respectively.